Al-Waste-Based Zeolite Adsorbent Used for the Removal of Ammonium from Aqueous Solutions - Ruth Sánchez-Hernández; Isabel Padilla; Sol López-Andrés; Aurora López-Delgado (International Journal of Chemical Engineering)
This work evaluates the use of a synthetic NaP1 zeolite obtained from a hazardous Al-containing waste for the removal of ammonium (NH4+) from aqueous solutions by batch experiments. Experimental parameters, such as pH (6–8), contact time (1–360 min), adsorbent dose (1–15 g/L), and initial NH4+ concentration (10–1500 mg/L), were evaluated. Adsorption kinetic models and equilibrium isotherms were determined by using nonlinear regression. The kinetic was studied by applying both the pseudo-first-order and pseudo-second-order models. The equilibrium isotherms were analyzed according to two-parameter equations (Freundlich, Langmuir, and Temkin) and three-parameter equations (Redlich–Peterson, Sips, and Toth). The results showed that the NH4+ uptake on NaP1 was fast (15 min) leading to a high experimental sorption capacity (37.9 mg/g). The NH4+ removal on NaP1 was a favorable process that followed the pseudo-first-order kinetic model. The NH4+ adsorption was better described by the Sips (54.2 mg/g) and Toth (58.5 mg/g) models. NaP1 zeolite from Al-waste showed good NH4+ sorption properties, becoming a potential adsorbent to be used in the treatment of contaminated aqueous effluents. Thus, a synergic effect on the environmental protection can be achieved: the end of waste condition of a hazardous waste and the water decontamination.